2016
DOI: 10.20944/preprints201608.0172.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Political Ecology of Chinese Large Dams in Cambodia: Implications, Challenges and Lessons Learnt from the Kamchay Dam

Abstract: Given the opportunities offered by foreign investment in energy infrastructure mostly by Chinese firms, the Government of Cambodia is giving high priority to developing hydropower resources for reducing energy poverty and powering economic growth. Using a "Political ecology of the Asian drivers" framework, this paper assesses China's involvement in the development of large dams' in Cambodia and its impacts on the access of natural resources such as water and energy by dam builders, local communities and the go… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 21 publications
(31 reference statements)
0
16
0
2
Order By: Relevance
“…Scholars warn that this short-sighted approach becomes legally relevant as it misrecognizes the planning and designing stage (Plummer Braeckman and Guthrie, 2016), or even politically and strategically sensitive when hydro plants are located close to international borders (Kuenzer et al, 2013;Middleton, 2012). Lastly, several scholarly reviews have found the governance of many hydro projects inadequate, leading to conflictive outcomes (Buechler et al, 2016;Kuenzer et al, 2013;Siciliano et al, 2016;Urban, 2014;Urban et al, 2015).…”
Section: Dams and Sustainabilitymentioning
confidence: 99%
“…Scholars warn that this short-sighted approach becomes legally relevant as it misrecognizes the planning and designing stage (Plummer Braeckman and Guthrie, 2016), or even politically and strategically sensitive when hydro plants are located close to international borders (Kuenzer et al, 2013;Middleton, 2012). Lastly, several scholarly reviews have found the governance of many hydro projects inadequate, leading to conflictive outcomes (Buechler et al, 2016;Kuenzer et al, 2013;Siciliano et al, 2016;Urban, 2014;Urban et al, 2015).…”
Section: Dams and Sustainabilitymentioning
confidence: 99%
“…Our research (Siciliano et al, 2016) showed the livelihoods of these villagers was negatively affected by the dam and that no compensation was paid. Crucially, the driving of the project by top levels of the Cambodian leadership resulted in due process often being sacrificed in pursuit of project completion.…”
Section: Cambodia's Kamchay Dammentioning
confidence: 81%
“…This research uses a conceptual framework we term Political Ecology of the Asian Drivers (Siciliano & Urban, 2017 ; Siciliano, Urban, Tan-Mullins, Lonn, & Kim, 2016 ), which combines the theories and approaches of political ecology with those of the Asian Drivers. The Political Ecology of the Asian Drivers framework is a hybrid approach that seeks to elucidate three broad research aims, analyzing the actors driving the internationalization of dam-building; the channels through which they engage; and the environmental, social, economic and political impacts on the ground.…”
Section: Conceptual Framework and Methodologymentioning
confidence: 99%
“…We also conducted 22 individual semi-structured interviews with community members and village chiefs. See also Siciliano et al ( 2016 ) for parts of the fieldwork.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation